Digital and Structured Psychological Interventions for Anxiety and Depression: A Narrative Review - Anwar, Mahmood (Sinergi International Journal of Psychology, 2024)
Psychological interventions play a crucial role in addressing mental health disorders, particularly anxiety and depression. This study examines the effectiveness of various intervention strategies, including cognitive behavioral therapy, mindfulness techniques, and digital interventions. A systematic literature review was conducted using databases such as Scopus and Google Scholar, with inclusion criteria focusing on studies published in the last five years. Findings indicate that structured psychological interventions significantly reduce symptoms of anxiety and depression. Digital interventions, particularly internet-based cognitive behavioral therapy, demonstrate high accessibility and effectiveness, though challenges such as dropout rates and varying responses persist. Social support and personalized approaches further enhance intervention outcomes. The study highlights the importance of integrating mental health services into broader healthcare systems, particularly in resource-limited settings. Policy recommendations include expanding mental health access, training professionals, and implementing culturally tailored interventions. Future research should explore long-term efficacy, optimize digital therapy engagement, and refine personalized treatment strategies. Enhancing accessibility and integrating evidence-based psychological interventions will be key to addressing global mental health challenges.